BEYOND DISBANDMENT OF ISLAMIST ORGANIZATION: EXAMINING THE ADAPTIVE RESISTANCE OF HIZBUT TAHRIR INDONESIA (HTI) - Herdiansah, Ari Ganjar; Wahidin, Danis; Saputra, Anugrah (JWP (Jurnal Wacana Politik), 2023)
The disbandment of Hizbut Tahrir Indonesia (HTI) in 2017 marked a significant shift in the dynamics of Islamist movements within Indonesia’s political landscape. Although officially banned, the HTI continued to operate in the shadows, employing various camouflage methods. This article analyzes how political dynamics led HTI to its outlawed status and how it adapted in pursuit of its goals amidst the challenges faced. By adopting a political opportunity structure and Islamist ideology as the theoretical framework with the case study as the method, this study scrutinizes HTI’s post-disbandment endeavors at the national level and delves deeper into cases in West Java, Yogyakarta, and East Java. The primary findings of this study reveal that the disbandment of HTI reflected the peak of incongruence between the anti-system ideology they embraced and Indonesia’s political structure. HTI’s ideological drive to exploit electoral events in 2016-2017 eventually put them at a threshold that the ruling authority perceives as a severe threat. HTI struggled to maintain its movement, mixing overt and covert operations, and facing significant pressures and constraints. Its strength is rooted in an Islamist ideology that integrates political and religious beliefs, supported by a disciplined structure. This resilience, seen as adaptive resistance, leverages tactical ingenuity and militancy in response to external pressures and the socio-cultural context in which they operate. Nevertheless, the disbandment has rendered it nearly impossible for HTI to reestablish its expansion in Indonesia’s political arena.